Understanding Markov-switching rational expectations models - Roger E.A. Farmer; Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2009)
We develop a set of necessary and sufficient conditions for equilibria to be determinate in a class of forward-looking Markov-switching rational expectations models, and we develop an algorithm to check these conditions in practice. We use three examples, based on the new Keynesian model of monetary policy, to illustrate our technique. Our work connects applied econometric models of Markov switching with forward-looking rational expectations models and allows an applied researcher to construct the likelihood function for models in this class over a parameter space that includes a determinate region and an indeterminate region.
Keywords: E5; 330; stability; nonlinearity; unique equilibrium; cross-regime indeterminacy; expectations formation; necessary and sufficient conditions; Rationale Erwartung; Markovscher Prozess; Neukeynesianische Makroökonomik; Geldpolitik; Theorie